EP577 Is it possible to develop a prediction model for lymphovascular space invasion in endometrioid endometrial cancer?. (1st November 2019) - Meydanli, MM; Aslan, K; Oz, M; Muftuoglu, KH; Yalcin, I; Engin-Ustun, Y
Abstract : Introduction/Background: The purpose of this retrospective study was to define a risk index that would serve as a surrogate marker of lymphovascular space invasion (LVSI) in women with endometrioid endometrial cancer (EC). Methodology: Final pathology reports of 498 women who underwent surgery with curative intent for endometrioid EC between January 2008 and June 2018 were retrospectively reviewed. Logistic regression was used to investigate clinicopathological factors associated with positive LVSI status. Independent risk factors for LVSI were used to build a risk model and 'risk of LVSI index' was defined as 'tumor grade x primary tumor diameter (PTD) x percentage of myometrium involved'. The scores used in the 'risk of LVSI index' were weighted according to the odds ratios assigned for each variable. The risk of LVSI index was noted for each patient. The diagnostic performance of the model was expressed as sensitivity, specificity, positive predictive value (PPV), negative predictive value (NPV), positive likelihood ratio (PLR) and negative likelihood ratio (NLR). Results: According to the 'risk of LVSI index', presence of LVSI was correctly estimated in 89 of 104 LVSI-positive women at a cutoff of 161.0 (sensitivity 85.5%, specificity 79.4%, NPV 95.4%, PPV 52.3%, PLR 4.15, NLR 0.18). The area under curve of the receiver-operating characteristics was 0.90 (95% Confidence Interval 0.87–0.93) at this cutoff. Conclusion: It seems possible to predict the presence of LVSI in women with endometrioid EC when the 'risk of LVSI index' is calculated. However, external validation of this model is warranted. Disclosure: Nothing to disclose.